Partisipasi Masyarakat dalam Pengelolaan Situs Megalitik Tutari - Zubair Mas’ud (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Management in archaeology usually called as archaeological remains advantaging. One of the cultural heritage that could manage is Tutari Megalitical site. Hope, the government as the facilitator must be give understanding about how important this archaeological remains. The public should be involved in the planning of cultural heritage management for archaeological remains preservation.